Apertura económica y producto sectorial: Alguna evidencia para la economía Argentina - Luis N. Lanteri (Atlantic Review of Economics, 2011)
– Orthodox and heterodox economists have promoted different liberalization measures in the economy in accordance with its vision for agriculture and manufacturing sectors. In this paper, we try to determine the impact of external terms of trade and domestic (the latter considers foreign trade policy) on the product of both sectors and unemployment rates. To this end, we use SVAR models with long-run restrictions and quarterly data for Argentina's economy, covering the period 1993:1-2011:1. It is noted that the variance of agricultural GDP is mostly explained by shocks in the external terms of trade, unlike manufacturing GDP which domestics are more relevant (other than their own shock). Moreover, the volatility of unemployment rates responds more to shocks in manufacturing GDP and in the domestic terms of trade.
Keywords: C1; F1; O1; 330